STUDY QUALITY OF WATER A RIVER AYAI AT AYAWIT DOWN TOWN, DISTRICT MEYAH – REGENCY OF TAMBRAUW IN THE PROVINCES OF WEST PAPUA - Supardi; Ceni Febi Kurnia Sari (JURUTERA - Jurnal Umum Teknik Terapan, 2022)
Natural resources, namely water, are abundant in Indonesia, which calls for all living things as a source of life. Therefore, abundant water resources must be protected and sustainably maintained, the use of water that is used properly and wisely by always taking into account the needs of children and grandchildren. The available water must be maintained in quantity and quality. Problems that often occur related to the availability of water, among others, the quantity of good water to use is limited while the need for water continues to increase, both for household, agricultural, and company needs. 2003). The decline in water quality is not only from industrial waste but also from household waste in the form of solid and liquid (Lallanilla, 2013). The purpose of this paper is to analyze the quality of river water and determine the status of the water quality of the Ayai River, Meyah District, Tambrauw Regency. The water quality of the Ayai River is based on the test results of several parameters. There is pollution downstream caused by the very high runoff, so it is contaminated with organic matter. The results of testing the water quality standards found that several parameters downstream of the Ayai River were lightly polluted. It was concluded that based on the calculation results of the Ayai river downstream of the river, there was pollution for parameters BOD5 6.4 mg/L, total phosphate 0.60 mg/L, zinc (Zn) < 0.065mg/L and Free Chlorine (CI2) < 0.12mg/ L which indicates that the water is in a polluted condition with these parameters.